2023
DOI: 10.1103/physrevlett.130.023003
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Mechanisms in Fermionic Josephson Junction

Abstract: We characterize numerically the dominant dynamical regimes in a superfluid ultracold fermionic Josephson junction. Beyond the coherent Josephson plasma regime, we discuss the onset and physical mechanism of dissipation due to the superflow exceeding a characteristic speed, and provide clear evidence distinguishing its physical mechanism across the weakly and strongly interacting limits, despite qualitative dynamics of global characteristics being only weakly sensitive to the operating dissipative mechanism. Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…Moreover, the W-SLDA Toolkit has been applied to a variety of problems. Results were documented in papers [26,28,35,[41][42][43][44]. We have also confirmed stability of the results with respect to size of the integration time step dt (all presented here results were obtained with dt = 0.0025e −1 F ).…”
Section: Higgs Mode Decay: (T D < T)supporting
confidence: 82%
“…Moreover, the W-SLDA Toolkit has been applied to a variety of problems. Results were documented in papers [26,28,35,[41][42][43][44]. We have also confirmed stability of the results with respect to size of the integration time step dt (all presented here results were obtained with dt = 0.0025e −1 F ).…”
Section: Higgs Mode Decay: (T D < T)supporting
confidence: 82%
“…To quantify these, we introduce flow and condensation energies. The former is just the kinetic energy associated with the flow, while the latter estimates the energy in the condensate (Cooper pairs) which uses a simple formula derived in the Bcs limit ( 32 ):…”
Section: Resultsmentioning
confidence: 99%
“…Our phenomenological model that captures these observations, in particular the identification of advective and diffusive modes along with the sigmoidal shape of I N (Δ μ + α c Δ T ), may help guide future microscopic theories of the system. While extensive research has been conducted on the entropy producing effects of topological excitations of the superfluid order parameter 8 , 12 , 21 , 39 , 41 , 45 49 , less attention has been given to their influence on entropy transport and the possible pair-breaking processes they can induce. Early studies of superconductors found that mobile vortices can advectively transport entropy by carrying pockets of normal fluid 50 with them 24 , 51 53 .…”
Section: Mainmentioning
confidence: 99%